Auctions versus bookbuilding: The effects of IPO regulation in Japan. Issue 1 (12th September 2022) - Lehmann, Timo; Weber, Matthias
Abstract: We analyze a regulatory change in the Japanese IPO market that created an abrupt shift from hybrid price‐discriminatory auctions to bookbuilding. We find that bookbuilding leads to higher underpricing than hybrid price‐discriminatory auctions. Furthermore, we find evidence that price accuracy tends to be higher for auctions than for bookbuilding. The results hold under a variety of OLS specifications and with regression discontinuity designs exploiting the abrupt change of the regulation.